The White Man's Burden: On the Effect of African Resistance to European Domination - Oasis Kodila-Tedika; Simplice Asongu; Matthias Cinyabuguma (African Governance and Development Institute (AGDI), 2016)
Are there contemporary development effects of African resistance to European domination? This question is the primary issue addressed by this inquiry. We establish that African resistance has had adverse effects on post-colonial African development and discuss possible channels of such causality. This relationship is robust to alternative model and to controlling for the outliers.
Keywords: N17; P48; O11; O43; O55; P14; P17; P51; 330; Africa; Colonization; Slavery; Development